Irrational Love: Taking Romeo and Juliet Seriously. Issue 3 (27th May 2022) - McKeever, Natasha; Saunders, Joe
ABSTRACT: This paper argues that there are important irrational elements to love. In the philosophical literature, we typically find that love is either thought of as rational or arational and that any irrational elements are thought to be defective, or extraneous to love itself. We argue, on the contrary, that irrationality is in part connected to what we find valuable about love. We focus on 3 basic elements of love: 1) Whom you love 2) How much you love them 3) How much of a role love plays in your life And in each case, we argue that love can be irrational and valuable.